Multiletramentos e ensino-aprendizagem de língua portuguesa: o livro didático de português do ensino fundamental - Bitencourt, Dinete Andrade Soares (2021)
With the theme Multiletrametos and Teaching-Learning of Portuguese Language: the Portuguese Didactic Book of Elementary Education, this work aims to verify if the multi-tools are explored from the texts / discursive genres of the didactic book Teacher Manual of the Tecendo Linguagens de Língua Portuguesa collection of the 9th year chosen by PLND for the three-year period 2018/2019/2020, de Oliveira et al. (2018). Its specific objectives are: to verify if the general and specific competences presented by the authors of the LD for the texts take into account the multi-tools and observe if the multimodal multi-tools are explored in the texts and activities of the teacher's manual LD. To achieve the general and specific objectives, a textbook unit was chosen. Theoretical support for descriptions and analyzes comes from the contributions of Bakhtin (1992), Geraldi (2015), Rojo (2012, 2013, 2016), Valentin Volóchinov (2017) Bakhtin's Circle, Tfouni, (2010), Bevilaqua (2013), Brazil - MEC - (2017 - 2018), PNLD 2018/2020, Lüdke, André (2018), Marconi & Lakatos (2017) among others. The methodology adopted focuses on qualitative bibliographic documentary research. The results indicate that the LD texts reach materiality by the themes, the multi-elements are present in the texts and in the skills listed by the authors for the analyzed texts, however the multimodal multi-elements are not taken into account in the exploration of activities.